Análise cinemática da marcha de pessoas com paralisia cerebral, classificadas segundo critérios do Comitê Paralímpico Internacional modalidade Atletismo - Rodrigues, Janaina de Oliveira (2013)
Studies concerning the analysis of march correlated to paralympic sport athletics are scarce. The purpose of this study was to determine, quantify and compare the kinematic changes in linear and angular parameters of human gait between groups with cerebral palsy, classified according to criteria the International Paralympic Committee in classes: T35 diplegic, T36 athetoid and ataxic and T37 hemiplegic. Measures of anthropometric variables, linear and angular kinematics were performed. For gait assessment was used movement system capture Optitrack and Motion Capture ARENATM Software. For statistical analysis, we performed an analysis of variance with post hoc Tukey test. The results showed significant differences ( p < 0,05) between groups for some linear variables such as Right Step Length, step width, Left Simple Support, Right Simple Support, Paralyzed Balance Left and Paralyzed Balance Right and some angular variables flexion-extension during initial support as: Left Hip Flexion and Paralyzed Left Hip Flexion, during the mid-stance: Right dorsiflexion and Paralyzed Right dorsiflexion and some angular variables of slope during the initial support: Left Leaning on the Trunk and Paralyzed Left Leaning on the Trunk during the final support Leaning right Hip, Left Leaning Trunk and Paralyzed Left Leaning Trunk and the average balance Right Leaning Trunk and Paralyzed Right Leaning Trunk. These results corroborate the differentiation made within the functional classification based on qualitative criteria by the International Paralympic Committee (IPC) between the three classes (T35, T36 and T37). There was a finding of \"subgroups\", in other words, people with different degrees of affections that belong to the same functional class according to the traditional classification of IPC. Depending on the degree of variability of occurrence within the same class, power would bring together those people in subclasses with similar abilities and therefore, contribute to a large number of Paralympic athletes achieve better results since these groups would be competing in more homogeneous.